A binary beta titanium superalloy containing ordered-beta TiFe, alpha and omega. (15th July 2021) - Jones, R.D.; Knowles, A.J.; Clegg, W.J.
Abstract: Alpha-beta titanium alloys excel for aeroengine applications but are typically limited to ~550°C. An alternative strategy is reinforcement with the ordered-beta TiFe intermetallic, toward 'β-Ti superalloys', however, there has been minimal study of TiFe precipitation in the binary system. Here, a Ti-20Fe (at.%) alloy was homogenised at 1050°C in the β-Ti phase field and aged at 600°C where the Fe supersaturation promoted TiFe precipitation. Curiously, as the TiFe volume fraction increased, the alloy hardness decreased, due to an interplay of mechanisms: (1) Fe solid solution strengthening, which reduces as the β-Ti Fe content falls to 16.2% on ageing; (2) ω precipitation strengthening, as ω-like incommensurate modulated domains were identified by transmission electron microscopy in the homogenised β-Ti parent phase and are suggested to change in size and structure after ageing, resulting in reduced ω-strengthening; (3) softening as softer TiFe and α-Ti phases precipitate from the harder ω‑strengthened β-Ti parent phase. Graphical Abstract: Image, graphical abstract